Análise da pevalência da osteoporose e dos principais fatores associados á perda óssea em portadores de cirrose - Santos, Lívia Alves Amaral [UNESP] (2015)
Cirrhotic patients are often compromised by nutritional deficiencies and loss of bone density through mechanisms as low ingestion of nutrients and lack of physical activity. The aim of this study was evaluate the prevalence of bone alterations and investigate if nutritional and hepatic tests would be related to the bone loss (osteoporosis or osteopenia) in cirrhotic outpatients from the Botucatu medical school (FMB-UNESP). Nutritional, hepatic and bone assessments were performed through anthropometric measurement, handgrip strength, dualenergy X-Ray absorptiometry (DXA) exam and laboratory tests. The study sample was composed by 129 subjects (77 men and 52 women), who were divided according to the Child-Pugh classification as follows: Child-Pugh A (69%), Child- Pugh B (24.8%) and Child-Pugh C (6.2%). The mean of the Model for End-Stage Liver Disease (MELD) score was 10.6 ± 3.99. The rates of osteoporosis and osteopenia were 31.01% and 32.56%, respectively. The results were assessed by backward linear regression model, showing that low handgrip strength, high parathyroid hormone (PTH) and low body mass index (BMI) were predictors of low t-score values in the lumbar spine. Additionally, only age was a predictor of low t-score values in the femoral neck. The model did not select the liver disease severity as a significant predictor of bone disease. As the liver cirrhosis is more aggressive in the lumbar spine, we suggest that handgrip strength, BMI and PTH should be tested in all cirrhotic patients to select the ones with higher risk of bone disease, in order to perform specific bone exams more often when these tests are altered, even in compensated cirrhosis